Modelling the performance of a Diffusion Absorption Refrigeration System - Yousuf, N; Biteau, E; Anderson, T; Gschwendtner, M; Nates, R (Australian PV Institute (APVI), 2014)
The diffusion absorption refrigeration cycle was first identified nearly a century ago but until relatively recently its application had been limited to niche cooling applications such as camping refrigerators. The diffusion absorption refrigerator consists of several main components: a generator and bubble pump (a thermal pump), a condenser, evaporator, and an absorber. Unlike a vapour-compression cycle, the cycle operates at a single pressure level and uses three working fluids: a refrigerant, an absorbant and an auxiliary gas that is used in the system to equalize the pressure. Furthermore, where the ubiquitous vapour-compression refrigeration cycle requires work input to drive the compressor, the diffusion absorption refrigeration cycle is a thermally driven process. This characteristic has seen the cycle begin to receive the renewed attention due to the potential for it to operate using solar thermal energy to drive it. In this work the performance of an ammonia/water/hydrogen diffusion absorption refrigeration cycle is modelled for steady state operating conditions. The results show that the performance of the cycle is dependent on a number of variables including: the temperature and amount of heat added at the generator, the effectiveness of the heat recovery loops and the mass flow of the ammonia. Furthermore, it shows that the performance of the bubble pump plays a significant role in determining the performance of the system and is an area that requires further attention.